Adopsi Inovasi Penggunaan Benih Varietas Unggul Baru (VUB) pada Budidaya Padi Sawah (Oryza Sativa L.) di Kecamatan Cisaat - Syahidul Alimudin; Nawangwulan Widyastuti; Dwiwanti Sulistyowati (Fakultas Pertanian, Universitas Timor, 2021)
Population growth continues to increase every year with a percentage increase of 1.19% per year in the 2016-2020 period. This is not in line with the availability of land in Indonesia which continues to decline. One of the efforts that can support the acceleration of increasing rice production is to use new high-yielding varieties (VUB) which have high yields, are resistant to major pests and diseases, or are tolerant to the local environment, and have special characteristics. This study was conducted to determine the level of adoption of the use of new superior varieties seeds in lowland rice cultivation, what factors affect the adoption rate, as well as to develop strategies for implementing the adoption of new superior varieties seeds in lowland rice cultivation. The method used is a descriptive method and multiple linear regression. Respondents were taken as many as 67 people who were determined intentionally (purposive sampling), namely farmers who became members of farmer groups and carried out rice cultivation business. The results showed that the adoption rate was included in the low category with a percentage of 81%. Factors that have a significant effect with a significant value of Conformity 0.026, Complexity 0.000, and Strictness 0.019. The strategy used in this research is to increase the adoption of innovation in the use of superior varieties of seeds, namely by conducting counseling to farmers by referring to the most critical and influential indicator, namely the suitability indicator.